RHETORICAL DEVELOPMENT IN INDONESIAN EFL STUDENTS’ ARGUMENTATIVE ESSAYS (RETAIN, 2015)
ABSTRACT Writing patterns are different among cultures if the language styles are also different, especially between English and Indonesian. However, some studies found that Indonesian students are capable of writing by using English pattern when they are taught in a writing course. Long after they have not been taught the English pattern, their writing patterns changes. This study reports that change. It is a qualitative content analysis study on 40 argumentative essays, written by 20 students of State University of Surabaya, which were analyzed. The results of this study show that the rhetorical developments of students’ essays become less linear after two years. This means that their study in an English writing course has successfully teach them to write following the English logic. Yet, these students cannot maintain their linear pattern over time. Key words: Rhetorical development, Writing pattern, Argumentative essay ABSTRAK Pola tulisan antar budaya berbeda jika gaya bahasa mereka berbeda pula, terutama antara Bahasa Indonesia dan Bahasa Inggris. Meski demikian, beberapa penelitian menunjukkan bahwa siswa Indonesia mampu menulis menggunakan pola Inggris ketika diajarkan pelajaran menulis bahasa Inggris. Sekian lama setelah mereka tidak diajarkan pola tulisan bahasa Inggris, pola tulisan mereka berubah. Penelitian ini membahas perubahan tersebut. Penelitian ini menggunakan metode konten analisis kualitatif pada 40 esai argumentasi yang ditulis oleh 20 mahasiswa Universitas Negeri Surabaya. Hasil penelitian ini menyebutkan bahwa langkah retorika mereka berkurang linearitasnya setelah dua tahun. Ini membuktikan bahwa pembelajaran menulis bahasa Inggris mereka berhasil membuat membuat siswa menulis menggunakan retorika Bahasa Inggris. Tetapi, siswa-siswa tersebut tidak mampu mempertakankan pola linear mereka selang beberapa waktu. Kata Kunci: Susunan Retorika, Pola menulis, esai argumentasi